2020
DOI: 10.1101/2020.10.12.335547
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Visual dysfunction predicts cognitive impairment and white matter degeneration in Parkinson’s disease

Abstract: Visual dysfunction predicts dementia in Parkinsons disease (PD), but whether this translates to structural change is not known. We aimed to identify longitudinal white matter changes in patients with Parkinsons disease and low visual function and also in those who developed mild cognitive impairment (MCI). We used fixel-based analysis to examine longitudinal white matter change in PD. Diffusion MRI and clinical assessments were performed in 77 patients at baseline (22 low visual function /55 intact vision; and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…Thalamic regions were amongst the highest contributors to this transition. Thalamic involvement has been previously described in visual hallucinations(56,71) and we recently showed longitudinal changes in grey and white matter within the medial mediodorsal thalamus(72). This provides further evidence of the thalamus as a key driver of network imbalance in PD-hallucinations(65,73).…”
Section: Discussionmentioning
confidence: 64%
“…Thalamic regions were amongst the highest contributors to this transition. Thalamic involvement has been previously described in visual hallucinations(56,71) and we recently showed longitudinal changes in grey and white matter within the medial mediodorsal thalamus(72). This provides further evidence of the thalamus as a key driver of network imbalance in PD-hallucinations(65,73).…”
Section: Discussionmentioning
confidence: 64%
“…It was reported that VI could predict CFI in patients with Parkinson's disease. [44][45][46] Gbessemehlan A 47 et al suggested that improving vision might be an easy way to decrease the incidence of cognitive disorders. Several ophthalmology studies reported similar results.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of structure and morphology, the microstructure and morphology of white matter as well as the macroscopic structure of patients with poor vision were more extensively changed than those with normal vision. 45 One hypothesis is that VI reduces the ability of the elderly to engage in activities that maintain health and leads to reduced brain stimulation, which may be a risk factor for cognitive decline. 49,50 Another hypothesis goes that both VA and cognitive decline may share the common cause, such as age, inflammation or deterioration of central nervous function.…”
Section: Discussionmentioning
confidence: 99%
“…49 We found that depression was also associated with visuoperceptual deficits which have also been shown to be associated with widespread macrostructural white matter degeneration. 39 It is most likely that PD depression is linked with these other non-motor PD features due to a shared aetiology of accelerated and more widespread Lewy body deposition in brain regions beyond the midbrain dopaminergic neurons.…”
Section: Discussionmentioning
confidence: 99%
“…38 We used this metric as our previous work in PD has shown FC to be a more sensitive measure of degeneration, compared to other fixel-based measures such as fibre density and combined fibre density and cross section. 39 FC was estimated for each fixel by calculating the distortion in fibre bundle cross-section required to warp the subject image to the template image.…”
Section: Fibre Cross-sectionmentioning
confidence: 99%